Association of Betel Leaf Chewing and Use of Tobacco with Development of Oral Cancer (Journal of Dhaka National Medical College & Hospital, 2015)
Background: Oral cancer is the 11th most common cancer in the world, 3rd most in Indian sub-continent and 20% of all cancer in Bangladesh. Oral cancer is increased with chewing betel leafwith or without tobacco. Approximately 90% of oral cancer can be attributed to tobacco chewing and smoking habits.Objectives:This study was conducted to find out the association of betel leaf chewing and use of tobacco with development of oral cancer.Methods:A hospital based case-control study was conducted on 204 patients (68 cancer patient as case and 138 subjects as control), 119 male and 85 female, age ranged from 18 to 80 years, attending at National Institute of Cancer Research and Hospital, Mohakhali, Dhaka over the period of one year, from July 2007 to June 2008. A pre-tested questionnaire was used to collect data by face-to-face interview of the respondents. Chi-square test and t-test were done to cheek for statistical significant association between different variables.Results:Statistically significant association was found between betel quid  chewing habit  and development of oral cancer. Significant association also was found between use of tobacco and development of oral cancer.Conclusion:Public health initiative should be taken to prevent use of tobacco and chewing betel leaf to prevent oral cancerJ.Dhaka National Med. Coll. Hos. 2015; 21 (01): 42-47